Achieving comparability of morphometric and model histogenetic-morphogenetic data using global optimization test functions. - Bolkhovitinov, A. S. (Морфологія / Morphologia / Morfologìâ, 2013)
Any theoretical construction in morphological modeling is useful only when it can be linked to the practice. Any formalism is not optimal for describing the processes of morphogenesis, if it is not comparable with the shape of tissue structures. Thus, it is necessary to find the best approximation for the correct comparison of the experimental and theoretical results. Proposed in this paper, the use of test functions for genetic algorithms, evolutionary programming, and swarm optimization for the approximation of the morphogenesis of cellular structures and their models is a mathematical step towards the implementation of the thesis of the analyzed article author (Gradov O.V., 2011), deduced not precise enough. There are other ways of analytical approximation for this case, but they have no fundamental differences in terms of their ease of use in mathematical biology. Achieved in this way comparability of morphometric and model histogenetic-morphogenetic data can be used in mathematical and morphological analysis and modeling in histology and embryology.